The Impact of ESG Ratings on Stock Price and Volatility: Evidence from LQ45, FTSE KLCI, and FTSE STI - Daffaliska Azaria Nugraha; Stylianos Asimakopoulos; Oktofa Yudha Sudrajat (Dinasti Publisher, 2025)
This study examines the impact of environmental, social, and governance (ESG) performance on stock returns and volatility in Southeast Asia, focusing on the LQ45 (Indonesia), FTSE KLCI (Malaysia), and FTSE STI (Singapore) indices from 2010 to 2022. Using composite ESG scores and individual E, S, and G scores, the research evaluates corporate sustainability performance and employs regression models to analyze their relationships with stock returns and volatility. The findings indicate that a higher combined ESG score is generally associated with lower stock returns and reduced volatility across the region. Among the individual ESG components, both environmental (E) and social (S) scores negatively impact stock returns, while the environmental (E) score also significantly reduces stock volatility. Governance (G) scores, however, show no significant effect on either returns or volatility. The study further explores how firm size and borrowing levels influence these relationships. For large firms, a higher ESG score boosts stock returns but lowers volatility. In contrast, smaller firms experience declines in both returns and volatility with increased ESG performance. When considering borrowing levels, firms with low debt benefit from higher ESG scores, which positively affect returns and modestly reduce volatility. Conversely, highly leveraged firms see decreased returns and increased volatility with higher ESG scores. These results underscore the nuanced relationship between ESG performance and financial outcomes in Southeast Asia, highlighting the importance of firm-specific characteristics. The study provides valuable insights for investors and corporate managers navigating the growing emphasis on sustainability in these emerging markets.